2011
DOI: 10.1111/j.1574-6968.2011.02351.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of trap formation in nematode-trapping fungi by a bacterium

Abstract: Three soil bacterial strains were identified as Chryseobacterium sp. TFB on the basis of their 16S rRNA gene sequences. Conidia of Arthrobotrys oligospora produced a few mycelial traps (MT) and conidial traps (CT) when cultured with bacterial cells that they did not produce when cultured with a bacterial cell-free culture filtrate. However, co-culture of A. oligospora with bacterial cells and bacteria-free filtrate simultaneously induced MT and CT in large amounts. With the increased concentration of bacteria-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 22 publications
0
12
0
2
Order By: Relevance
“…(McClure, 1989 ); by inducing the activity of other nematode antagonists, such Chryseobacterium spp. that induce trap formation in Arthobotrys oligospora (Li et al, 2011 ); by suppressing disease severity, such Chryseobacterium spp. (Liu et al, 2014 ); or by parasitizing RKN eggs, such Fusarium equiseti and Cladosporium spp.…”
Section: Discussionmentioning
confidence: 99%
“…(McClure, 1989 ); by inducing the activity of other nematode antagonists, such Chryseobacterium spp. that induce trap formation in Arthobotrys oligospora (Li et al, 2011 ); by suppressing disease severity, such Chryseobacterium spp. (Liu et al, 2014 ); or by parasitizing RKN eggs, such Fusarium equiseti and Cladosporium spp.…”
Section: Discussionmentioning
confidence: 99%
“…oligospora, a nematophagous fungus, captures nematodes by using adhesive polymers present on traps which form a three dimensional network [19]. Recent studies revealed that some of bacteria could induce trap for mation in A. oligospora [20]. In our present experi ment, the filtrate of bacteria A. faecalis YMF 3.175 induced trap formation in this fungus.…”
Section: Bioassay For Inducing Trap Formation In a Oli Gospora By Amentioning
confidence: 49%
“…attached to hyphae of A. oligospora and their metabolites (Li et al . ). The data produced in this study are consistent to previous studies and indicate that either bacteria or their metabolites should attract a greater attention in the future, considering their potential effects on nematodes ecology.…”
Section: Resultsmentioning
confidence: 97%